Dheepan [videorecording (DVD)] - Audiard, Jacques; Ṣōpā Cakti; Srinivasan, Kalieaswari; Vinasithamby, Claudine (Criterion collection, 2017)
To escape the civil war in Sri Lanka, a former soldier, a young woman and a little girl pose as a family. They end up settling in a housing project outside Paris. Even though they barely know one another, they try to build a life together.